Dual-Focuses Metalens for Copolarized and Cross-Polarized Transmission Waves - Ru Ji; Kejian Chen; Yujie Ni; Yanan Hua; Kaiwen Long; Songlin Zhuang (Advances in Condensed Matter Physics)
Metasurfaces can reshape the wavefront in the desired manner by manipulating the phase profile and amplitude of the incident wave. In this paper, we demonstrate an ultrathin terahertz metalens based on our designed resonator structure, where the polarization state can be converted to the orthogonal direction and the parabolic phase profile is designed covering a 2π phase region. Many functional metalenses are also engineered to meet the demand of focusing, dual-polarization confocal, and dual focuses for orthogonal polarization in the frequency range from 0.65 to 0.8 THz. The presented metalenses can provide potential applications in terahertz communications and imaging systems.